Жоғары оқу орнында оқу үрдісінде студенттердің психологиялық мәдениетінің қалыптасуы - Орумбаева, А.Б. (My University, 2013)
In this article the problem of the formation of the psychological culture of the students ofthe height educational institution is viewed in depth. To date,higher educationfor students -this isknowledge neededthroughout life, so the level of psychologicalculture of the futureof educational psychologistsmust meetthe changing socioeconomic and professionallearning environment.